Body mass index and parasympathetic nervous system reactivity and recovery following graded exercise. Issue 1 (10th December 2018) - Gerardo, Gina M.; Williams, DeWayne P.; Kessler, Michael; Spangler, Derek P.; Hillecke, Thomas K.; Thayer, Julian F.; Koenig, Julian
Abstract: Objectives: The present study sought to expand upon prior investigations examining patterns of vagally mediated heart rate variability (vmHRV) and perceived exertion as a function of body mass index (BMI) in response to and recovery from exercise. Methods: Participants underwent a resting (baseline) period, followed by a graded exercise protocol on an ergometer with ascending difficulty stages, and finally another resting (recovery) period. Individuals were stratified into three BMI groups: low, moderate, and high . Results: Individuals in the high BMI group exhibited a significantly greater decrease in vmHRV from baseline to graded exercise in comparison to the moderate BMI group. Individuals in the high BMI group also showed significantly lower vmHRV at recovery compared with baseline than individuals with moderate BMI; indicating that the high BMI group's vmHRV did not recover to the degree of those in the moderate BMI group. No significant results regarding vmHRV were found in the low BMI group. Of note, BMI and perceived exertion during the recovery period were positively associated. Results also showed a significant negative association between vmHRV and perceived exertion at each grade of exercise. There was no significant association between vmHRV and perceived exertion during baseline or recovery. Conclusions: This report extends prior research studying BMI and patterns of vmHRV reactivity in the domain of physical exercise. Our data contribute to previous reports suggesting that high BMI can lead to maladaptive patterns of vmHRV reactivity to and recovery from physical exercise.